TỔNG HỢP, NGHIÊN CỨU CẤU TRÚC PHỨC CHẤT CỦA NIKEN(II) VÀ PALADI(II) VỚI 4-PHENYL THIOSEMICACBAZON AXETOPHENON - Châu, Trịnh Ngọc; Bích Phương, Nguyễn Thị; Hà, Nguyễn Văn (Vietnam Journal of Chemistry, 2012)
This paper reports the synthesis and spectral studies of palladium and nickel with acetophenone 4-phenyl thiosemicarbazones (Hpthacp). The ligand and complexes are characterized by means of chemical analysis, IR, ESI-MS and 1H-NMR spectroscopy. The obtained data show that in M(pthacp)2 (M: Ni, Pd) complexes, the ligand acts as anionic bidentate ligands, two coordinate bonds realize through S and N(1) atoms. Keywords: Palladium complex; 4-phenyl thiosemicarbazone.